Gilda Joyce : the ghost sonata - Allison, Jennifer (Dutton Children's Books, 2007)
Gilda Joyce's best friend Wendy Choy qualifies to compete in an international piano competition in Oxford, England, and Gilda is determined to go as well--as a page turner.